African Developments: continental conflict management – a glass half full or half empty? - Stefan Gänzle; Benedikt Franke (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
The emergence of the African Peace and Security Architecture (APSA) is one of the most important recent developments in Africa. The institutional setting for fostering peace and security on the continent has been created by the efforts of African governments to engage in comprehensive continental integration. These endeavours date back to the late 1990s and culminated in the establishment of the `African Union' (AU) as a successor to the Organisation of African Unity (OAU) in 2002. The APSA is among the AU's most prominent features and includes a Peace and Security Council, an African Standby-Force and a Continental Early Warning System. Together with the AU's Charter, which supports innovative legal doctrines such as human security and responsibility- to-protect, these institutions provide a significant conceptual, meaningful and practical advance. However severe institutional and financial shortcomings within some of the APSA features remain. Hence, the international community, and in particular the European Union, which is the most important donor to the AU, should increase its capacity-building commitments to both the continental as well as the regional pillars of inter-African cooperation. More importantly, they should seek to strengthen the dialogue with the member states of the AU, in particular those who are members of the Peace and Security Council. Overcoming three shortcomings is of critical importance: First, the lack of capacity of AU institutions; second the absence of sufficient political will by a majority of Africa's States and third changes in international support. Yet, for the time being the APSA provides for some legitimate actors on the continent and is Africa's best bet thus far for improved continental cooperation in the area of conflict management.
Keywords: 330